2022
DOI: 10.3390/biom12111682
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Regenerative Therapy Using rhFGF-2 and Deproteinized Bovine Bone Mineral versus rhFGF-2 Alone: 4-Year Extended Follow-Up of a Randomized Controlled Trial

Abstract: The aim of this study was to evaluate longitudinal outcomes of recombinant human fibroblast growth factor (rhFGF)-2 plus deproteinized bovine bone mineral (DBBM) therapy in comparison with rhFGF-2 alone for treating periodontal intrabony defects. This study describes 4-year follow-up outcomes of the original randomized controlled trial. Intrabony defects in periodontitis patients were treated with rhFGF-2 (control) or rhFGF-2 plus DBBM (test). Clinical, radiographic, and patient-reported outcome (PRO) measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Two possible scenarios arise in such cases: multiple sites in the same patient undergoing the same treatment or different ones. [ 67 , 70 , 85 , 93 , 101 , 113 , 116 , 124 , 129 , 132 , 139 , 154 ] Some clinical trials do not specify further how this randomization is performed. [ 81 , 94 , 147 , 233 ] This approach might introduce further complexities when interpreting the results, and it has been found that most trials in periodontology could benefit from better methodological and reporting quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two possible scenarios arise in such cases: multiple sites in the same patient undergoing the same treatment or different ones. [ 67 , 70 , 85 , 93 , 101 , 113 , 116 , 124 , 129 , 132 , 139 , 154 ] Some clinical trials do not specify further how this randomization is performed. [ 81 , 94 , 147 , 233 ] This approach might introduce further complexities when interpreting the results, and it has been found that most trials in periodontology could benefit from better methodological and reporting quality.…”
Section: Discussionmentioning
confidence: 99%
“…[ 203 , 204 ] Clinical trials have extensively proven the efficacy of REGROTH Dental Kit, improving both clinical and radiographic outcomes. [ 129 , 139 , 164 , 201 , 205 , 206 ] Interestingly, the efficacy of rhFGF‐2 was not affected by patients’ age, sex, type of tooth, and classification of bone defects. [ 206 ] Moreover, in a randomized controlled clinical study on 2‐ and 3‐wall intra‐bony defects, REGROTH Dental Kit (Group 1) was found to be superior to Emdogain (Group 2) and OFD (Group 3) in radiographic bone fill after 36 weeks (Group 1: 34.37 ± 24.42%, Group 2: 23.29 ± 25.11%, Group 3: 13.30 ± 20.60%).…”
Section: Review Of Regenerative Products In Periodontal Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 In contrast, growth factors such as FGF-2, PDGF, and bone morphogenetic protein-2, in conjunction with various biomaterials, have also demonstrated improved clinical outcomes. 25 , 26 , 27 , 28…”
Section: Clinical Advancementsmentioning
confidence: 99%
“…Soluble dECM is usually used in dental-derived dECM, such as porcine pulp dECM, dog periodontal membrane dECM, and even human dental capsule dECM. However, non-dental dECM, such as porcine SIS, acellular amnion, etc., needs to increase additional biological signals to promote periodontal regeneration, such as fibroblast growth factor [ 65 ], platelet fibrin [ 66 ], and other cytokines and mesenchymal stem cells, such as those related to periodontal regeneration, such as PDLSCs, BMSCs, DFSCs, ADSCs, and others [ 13 ].…”
Section: Application Of Decm Of Different Forms In Periodontal Regene...mentioning
confidence: 99%